Effects of various storage temperature and storage time on vitamin E levels of fish muscle - Arslan, A; Gonulalan, Z; Sarigol, C; Naziroglu, M; Aksakal, M (Scientific Technical Research Council Turkey, 1997)
This study was aimed to determine the effects of various storage temperatures and storage periods on vitamin E levels of fsh muscle. For this purpose fish samples (Onchorhynchus mykiss, Cyprinus carpio L. and Capoeta trutta) were stored at -12 and -18 degrees C for 17 weeks and vitamin E levels were analysed at the beginning of 0, 2, 4, 6, 8, 10, 12 and 17 weeks. At the end of the storage period average vitamin E levels in Onchorhynchus mykiss samples stored at -12 and -18 degrees C were 266.7+/-76.7 mu g/100 g (711.3-52.4 mu g/100 g) 378.8+/-52.9 mu g/100 g (711.3+/-228.8 mu g/100 g); these values in Cyprinus carpio L. were 427.4+/-72.2 mu g/100 g (787.4-165.2 mu g/100 g), 555.9+/-68.9 mu g/100 g (787.4-248.2 mu g/100 g) and in Capoeta trutta were 317.2+/-76.3 mu g/100 g (656.4-78.6 mu g/100 g), 169.8+/-14.8 mu g/100 g (656.4-169.8 mu g/100 g) respectively. Vitamin E loss was more in samples stored at -12 degrees C. Decrease in vitamin E levels were statistically significant in Onchorhynchus mykiss samples at the beginning of 6 th, in Cyprinus car pio L. samples at the beginning of 2 nd, in Capoeta trutta at the beginning of 8 th week (p<0.001, p<0.01, p<0.05).
Farkli muhafaza sicakli?i ve sürelerinin balik eti vitamin E miktarina etkisi
Keywords: fish; muscle; storage; vitamin E level